PESTICIDES - A PROBLEM IN ROMANIA'S AGRICULTURE? - Agatha POPESCU; Cristiana TINDECHE; Alina MĂRCUȚĂ; Liviu MĂRCUȚĂ; Adelaida HONȚUȘ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the use of pesticides in Romania in the period 2007-2020, based on the official statistical data by type of pesticide, at the national and territorial level, and using fixed and structural indices, concentration indices and time and spatial comparisons. In the year 2020, pesticides were applied on larger surfaces than in 2007 and they accounted for 3.88 million ha for herbicides, 2.39 million ha for fungicides, and 2.34 million ha for insecticides. But, the total consumption decreased by 26% for insecticides and by 23% for herbicides, but it increased by 8.2% in case of fungicides. The national mean consumption of pesticides per ha declined and in 2020 accounted for 0.27 kg a.s. insecticide, 0.75 kg herbicide and 0.76 kg fungicide. Romania comes on the last position in the EU for the smallest average consumption 0.8 kg a.s. pesticide per ha and also for the risk indicator 1 equal to 48. he largest areas where pesticides are applied in the territory are in South Muntenia, West, South East and South West Oltenia micro-regions. Total consumption differs from a region to another as follows: insecticides are much more consumed in South West Oltenia, South Muntenia, North East, South East and West, fungicides are especially applied in South East, North East, Center and West, and herbicides are predominantly utilized in North East, South East, North West, South West Oltenia, and West. The average consumption per ha, over the national mean, is higher in the following regions: insecticides in North West, South West Oltenia, Center and North West, fungicides in the Center, Bucharest-Ilfov, South East and North East and herbicides in North East, North West and Center regions. The values of the concentration indices Herfindahl-Hirschman, Gini-Struck and Concentration coefficient proved that in 2020, Romania was characterized by a relative moderate concentration of the use of pesticides. As a conclusion, pesticides have to be used taking into consideration the local conditions at the regional level and at farm level. Farmers have to evaluate the problems and make the best decision regarding what type of pesticide to use, on what surface, which is the suitable dose per ha, how many treatments are required etc. The EU regulations regarding pesticides imposes a strict control and use of the approved pesticides for compiling with the European the Green Deal.